Plato and myth : studies on the use and status of platonic myths - Collobert, Catherine. (Mnemosyne, Supplements, 2012)
This volume seeks to show how the philosophy of Plato relates to the literary form of his discourse. Myth is one aspect of this relation whose importance for the study of Plato is only now beginning to be recognized. Reflection on this topic is essential not only for understanding Plato's conception of philosophy and its methods, but also for understanding more broadly the relation between philosophy and literature. The twenty chapters of this volume, contributed by scholars of diverse backgrounds and approaches, elucidate the various uses and statuses of Platonic myths in the first place by reflecting on myth per se and in the second place by focusing on a specific myth in the Platonic corpus.